FREQUENCY AND AETIOLOGY OF PRURITIS IN ADMITTED PATIENTS IN A MEDICAL WARD OF MAYO HOSPITAL, LAHORE - Mahboob, Fatima (Journal of Ayub Medical College Abbottabad, 2004)
Background: Prutitis or itching is a common complaint. It can be due to many dermatological and medical illnesses. This study was conducted to find out presence of pruritis in different diseases in patients admitted in a medical ward and to determine whether pruritis is more common due to medical causes or dermatological causes. Methods: All patients admitted in North Medical Ward, Mayo Hospital, Lahore during March 2002 to November 2002 were included in the study. Complete medical history especially history of pruritis was taken. Physical examination was performed to diagnose the primary illness and to find cause of pruritis when present. Results: 740 patients were included in the study. Sixty (8.1%) patients complained of pruritis. 5.4% had pruritis due to skin conditions. 2.7% had pruritis due to medical illnesses. Conclusion: The patients admitted in medical ward are having pruritis mainly due to medical diseases but skin conditions should not be ignored. KEY WORDS: Pruritis, itching, scabies